Translanguaging and scaffolding as pedagogical strategies in a primary bilingual classroom. Issue 3 (3rd July 2022) - Pinho Feller, Nayalin
ABSTRACT: This study aimed at investigating when, and for which purposes, teachers and pupils translanguaged in a third-grade classroom [8–9 year olds] in a private bilingual school in northern Portugal. It also aimed at highlighting effective scaffolding strategies developed by the teachers in the Natural and Social Sciences (NSS) and English Language (EL) lessons. Classroom observations were conducted for a six-month period. Data was collected through participant-observation, using a single case study design with multiple embedded units of analysis. Data analysis was performed qualitatively by analysing language use in fieldnotes from classroom observations, audio recordings of NSS and EL lessons, and a pupil survey and also through content analysis for teachers' written reflections. A total of 26 categories were derived under different types of translanguaging and scaffolding strategies used both by the teachers and the pupils. It was found that translanguaging was used for the teaching of content and to establish communication, and it was both teacher-directed and pupil-directed. Findings have implications for educators when considering how translanguaging can be used as a pedagogical tool in Content and Language Integrated Learning (CLIL) classrooms.